Predictors of PDA Treatment in Preterm Neonates Who Had Received Prophylactic Indomethacin - Louis, Deepak; ElSayed, Yasser N.; Ojah, Cecil; Alvaro, Ruben; Shah, Prakesh S.; Dunn, Michael; for the Canadian Neonatal Network Investigators (American Journal of Perinatology, 2018)
Objective To identify clinical factors those predict the need for patent ductus arteriosus (PDA) treatment in preterm neonates who had received prophylactic indomethacin.Patients and Methods Preterm neonates with <28 weeks' gestational age admitted to level III neonatal intensive care units (NICUs) in Canada between 2010 and 2015 and who had received prophylactic indomethacin were included. Primary outcome was surgical ligation of PDA, while secondary outcomes were any PDA treatment and common neonatal morbidities.Results Of the 7,024 eligible neonates, 843 (12%) neonates had received prophylactic indomethacin. Of them, 84 neonates (10%) required surgical ligation while 367 neonates (44%) received medical or surgical treatment for PDA. Logistic regression analyses identified gestational age (odds ratio [OR]: 0.71, 95% confidence interval [CI]: 0.58–0.87) and outborn status (OR: 2.07, 95% CI: 1.09–3.93) as predictors for surgical ligation. Maternal hypertension (OR: 0.57, 95% CI: 0.37–0.89), rupture of membranes (ROM) ≥24 hours (OR: 0.68, 95% CI: 0.48–0.96), and surfactant treatment (OR: 1.70, 95% CI: 1.09–2.66) were predictors for medical or surgical treatment of PDA.Conclusion In extremely preterm neonates who had received prophylactic indomethacin, gestational age and outborn status were predictors for surgical ligation of PDA, while maternal hypertension, ROM ≥24 hours, and surfactant treatment were associated with the medical or surgical treatment of PDA.
Keywords: preterm neonate; PDA treatment; prophylactic indomethacin; predictors; surgical ligation